UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEXT RECOUNT SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE DALAM PEMBELAJARAN BAHASA INGGRIS DI KELAS VIII-4 SMPN 5 TANJUNG MORAWA - Suratik, Suratik (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
Subjects were students of class VIII SMP Negeri 4 5 Tanjung Morawa Academic Year 2015/2016 the number of students as many as 34 people. This study consisted of two cycles. In cycle I spent 3 meetings and the second cycle spent 2 meetings. The instrument used was a test and non-test. Mechanical tests students ability to write text recount the form of a written test on each cycle, while the non-test techniques using instruments of observation of student activity during learning. The results showed an increased ability to write text recount of students learning English in the first cycle and the second cycle. Once the act is done in two cycles recount text writing ability of students has increased with the average - average grade in the first cycle obtained 69,41dengan success percentage 58.82% while the average - average grade on the second cycle was obtained 75.58 with a 85.29% success persentase , Similarly, the results of nontest namely an increase in development activity of students during the learning takes place, it is seen from almost all indicators of student activity has been achieved.Â Key Words: Learning Model PICTURE and PICTURE, Text Recount